THE INFLUENCE OF SELF CONCEPT, ACHIEVEMENT MOTIVATION, AND LEARNING STYLE TOWARD MATHEMATICS DISPOSITION AND MATHEMATICS LEARNING RESULTS OF GRADE XI STUDENTS AT SMAN IN MAKALE CITY - Ersi Cresli (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2016)
High learning result in Mathematics is a benchmark of students’ success in Mathematics learning. The students need positive characters and attractiveness to achieve high learning results in Mathematics. Moreover, the students need self concept, achievement motivation, and learning style as well. The research aims at examining the extent of the influence of self concept, achievement motivation, and learning style toward mathematics disposition and the students mathematics learning results in Mathematics of grade XI students at SMAN (public senior high schools) in Makale city. The research is ex-post facto. The populations of the research were the students of grade XI at SMAN in Makale city. The samples were obtained by using cluster proportional random sampling with the total of 171 students. The data collection technique employed self concept questionnaire, achievement motivation questionnaire, learning style questionnaire, mathematics disposition questionnaire, and mathematics learning results test. The data of the research was analyzed by using descriptive and multiple regression analysis. The results of the research reveal that: (1) most students of grade XI at SMAN in Makale city have self concept, achievement motivation, mathematics disposition and mathematics learning results, which is in medium category and visual learning style; (2) self concept has positive influence toward mathematics disposition with contribution 28.9% and give no positive influence toward mathematics learning results with contribution 2.5%. Achievement motivation has positive influence toward mathematics disposition with contribution 47.2% and give no positive influence toward mathematics learning results with contribution 14.9%. There is no influence of learning style both toward mathematics disposition and mathematics learning results. Self concept, achievement motivation, and learning style collaboratively explain approximately 51% of mathematics disposition variation and 2% of mathematics learning results variation. After the development of discussion, self concept gives contribution 15% toward mathematics learning results through mathematics disposition